MEMBINCANG GERAKAN ISLAM TRANSNASIONAL - Eko Kurniawan Wibowo (Diegesis : Jurnal Teologi, 2019)
Indeed Islam is a transnational religion. This understanding of transnational nature is based on the nature of a missionary Islam. The desire to convert people outside of Islam is a duty to Muslims or so called da'wa. Problems arise when the transnational Islamic movement changes and is understood as a political movement to unite Muslims in one territory or one country. The unity of Muslims under the umbrella of one country or called the islamiyya caliphate becomes the ambition of the transnational Islamic movement. The goal of re-establishing the Islamic Caliphate was a way to restore the glory of Islam which is currently being oppressed by the West.